PENGARUH PENGGUNAAN SMARTPHONE TERHADAP MINAT MENGIKUTI PEMBELAJARAN PJOK PESERTA DIDIK KELAS TINGGI SD NEGERI 1 LANGKAPURA KOTA BANDAR LAMPUNG - Tian Khansa, Andrienne; Wicaksono, Lungit; Jaya Sumantri, Riyan; Siswoyo, Joan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of smartphone use on the interest in participating in physical education lessons among upper grade students at SD Negeri 1 Langka Pura Kota Bandar Lampung. This study used a descriptive quantitative method with a population of 345 upper grade students, namely grades IV, V, and VI. using a random sampling technique of 10% using the Slovin formula, resulting in a sample of 78 students. The data collection technique in this study used a questionnaire with a Likert scale, and the data analysis technique used was descriptive statistical analysis of percentages. Based on the results of the simple regression test, an R Square value of 0.115 was obtained with a significance level of p = 0.002<0.05, which means that there is a significant effect between smartphone use and interest in participating in PJOK learning. This value shows that smartphone use contributes 11.5% to the variation in students' interest in participating in PJOK learning, while the rest is influenced by other factors.